Generating finite state machines from abstract state machines - Grieskamp, Wolfgang; Gurevich, Yuri; Schulte, Wolfram; Veanes, Margus (ISSTA 2002, 2002)
We give an algorithm that derives a finite state machine (FSM) from a given abstract state machine (ASM) specification. This allows us to integrate ASM specs with the existing tools for test case generation from FSMs. ASM specs are executable but have typically too many, often infinitely many states. We group ASM states into finitely many hyperstates which are the nodes of the FSM. The links of the FSM are induced by the ASM state transitions.